'It′s good enough': Swedish general dental practitioners on reasons for accepting substandard root filling quality. (24th February 2017) - Dahlström, L.; Lindwall, O.; Rystedt, H.; Reit, C.
Abstract: Aim: The concept of 'good enough' is central and necessary in the assessment of root filling quality. The aim was to explore the concept by analysing reasons and arguments for the acceptance or rejection of substandard root filling quality as reported by general dental practitioners (GDPs) in Sweden. Methodology: The study was designed as a qualitative and exploratory study based on seven videotaped focus group interviews analysed by means of qualitative content analysis. Thirty‐three GDPs employed in the Public Dental Health Service in Gothenburg, Sweden, participated (4–6 GDPs/interview). In all, nine predetermined questions were followed. Before each focus group, the participants received radiographs of 37 root fillings and were asked to assess the root filling quality. The three cases representing the most divergent assessments served as a basis for the discussion. The cases were presented without clinical information; the dentists would relate to the cases as being just root filled by themselves. Results: The radiographs did not provide a sufficient basis for decisions on whether or not to accept the root filling. This study emphasized that dentists did not primarily look for these arguments in the technical details of the root filling per se, but instead, they considered selected features of the contextual situation. The GDPs constantly introduced relevant ' ad hoc considerations' to account for the decisions they made. These contextual considerations were related to aspects of pulpal and periapical disease, risks (e.g. technical complications) or to consumed resources (personal and/or economic). Conclusions: It was obvious that the concept of 'good enough' does not exist as a general formula ready to be applied in particular situations. Instead, it is necessarily and irremediably tied to contextual properties that emerge from case to case.